Proceedings of the Seventh New England (Northeast) Bioengineering Conference, March 22-23, 1979, Rensselaer Polytechnic Institute, Troy, New York - Ostrander, Lee E. (Pergamon Press, 1979)
Proceedings of the Seventh New England (Northeast) Bioengineering Conference.